Manajemen Komunikasi Keluarga Saat Pandemi COVID-19 - Ana Kuswanti; Munadhil Abdul Muqsith; Anna Gustina Zainal; Selly Oktarina (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractThis article wants to explain that the Coronavirus Disease or COVID-19 pandemic disrupts the structure of family life. Since the government suppressed physical distancing, it indirectly allowed almost 24 hours to be at home. The COVID-19 pandemic greatly tested family resilience. Positively, the impact of independent quarantine gives time to get to know each other deeply among family members. On the other hand, the more often family members meet increases boredom, which then causes friction to occur. This paper writes how the family communication management strategy when Pandemic COVID-19 to create a harmonious and prosperous family, conduct interpersonal communication, responsibility for the environment and family, intensity and direction of communication with a harmonious atmosphere, healthy parenting even in a physical atmosphere distancing or guarding the distance according to government recommendations. Keywords: family communication management, COVID-19 pandemic, family resilience AbstrakArtikel ini ingin menjelaskan bahwa pandemik Coronavirus Disease atau COVID-19 mendistrupsi tatanan kehidupan keluarga. Sejak pemerintah menekannya physical distancing atau penjagaan jarak secara tidak langsung memberikan waktu nyaris 24 jam berada di rumah. Pandemi COVID-19 sangat menguji ketahanan keluarga. Secara positif, dampak karantina mandiri memberi waktu untuk saling mengenal secara mendalam antar anggota keluarga. Disisi lain, semakin sering anggota keluarga bertemu meningkatkan rasa jenuh yang kemudian menimbulkan gesekan terjadi. Tulisan ini menulis bagaimana strategi manajemen komunikasi keluarga saat Pandemi COVID-19 sehingga tercipta keluarga yang harmonis dan sejahtera, melakukan komunikasi antar pribadi, tanggung jawab pada lingkungan dan keluarga, intensitas dan arah komunikasi dengan atmosfir yang harmonis, pola asuh hidup sehat walaupun dalam suasana physical distancing atau penjagaan jarak sesuai anjuran pemerintah. Kata kunci: manajemen komunikasi keluarga, pandemik COVID-19, ketahanan keluarga